2009
DOI: 10.1002/hep.23193
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism in the Endoplasmic Reticulum Mannosidase I (MAN1B1) Gene Is Not Associated with Liver Disease in Individuals Homozygous for the Z Variant of the Alpha1-Antitrypsin Protease Inhibitor (PiZZ Individuals)†

Abstract: References

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
(4 reference statements)
0
1
0
Order By: Relevance
“…Consistent with this hypothesis, a candidate genesequencing study of endoplasmic reticulum (ER) mannosidase I (ERManI), which facilitates the degradation of misfolded secreted proteins (Hosokawa et al 2003;Wu et al 2003), suggested that differences in ERManI expression are associated with earlier age-of-onset of end-stage liver disease ). However, because of the small number of samples available for study, the significance of this association has been challenged (Chappell et al 2009;Pan and Sifers 2009). Even if the ERManI polymorphism does not prove to be a clinically significant modifier of ATD, there are likely to be many other factors that modify ATD-associated liver disease.…”
mentioning
confidence: 99%
“…Consistent with this hypothesis, a candidate genesequencing study of endoplasmic reticulum (ER) mannosidase I (ERManI), which facilitates the degradation of misfolded secreted proteins (Hosokawa et al 2003;Wu et al 2003), suggested that differences in ERManI expression are associated with earlier age-of-onset of end-stage liver disease ). However, because of the small number of samples available for study, the significance of this association has been challenged (Chappell et al 2009;Pan and Sifers 2009). Even if the ERManI polymorphism does not prove to be a clinically significant modifier of ATD, there are likely to be many other factors that modify ATD-associated liver disease.…”
mentioning
confidence: 99%